TRANSFORMASI HUBUNGAN PEMASARAN DI ANTARA PELAKU AGRIBISNIS MANGGA MELALUI JARINGAN PASAR MODERN - Hesty Nurul Utami; Agriani Hermita Sadeli (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Market access development for agricultural products has uncoverd various new marketing networks for many local agricultural commodities. Agribusiness tropical fruits, such as mangoes, has gained substantial market potentials in market access development for domestic and global markets. The study explores how relationship marketing amongst agribusiness actors of mango commodity using modern market networks with relational marketing orientation and how value exchange occurs amongst these market actors of mango commodity in modern market chains. An inductive research method was used in this study by employing in-depth interviews, and data were analysed qualitatively using descriptive analysis. The results indicate the marketing transformation of mango commodity using modern market channels, such as supermarket and export markets, related to relationship marketing amongst the market actors that led to more relational marketing. The exchange value that occurred through this relational marketing has proposed market certainty, risk reduction, knowledge sharing amongst market actors to fulfil customer needs, and competitive solutions that benefit the involved business actors. This study proposes theoretical and practical contributions as the basis for concept development and implementation of relational marketing in the agribusiness context.